Efektivitas Permainan Tradisional terhadap Hasil Belajar Matematika SD : Literature Review - Muhammad Awal Nur; Nurhafidzah Nurhafidzah (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Mathematics is a basic subject that is often perceived as difficult, and many students experience difficulties in achieving good grades in mathematics tests. This study aims to analyze the effect of integrating traditional games into mathematics learning on improving the learning outcomes of elementary school students through a literature review approach. Data sources were obtained from various academic databases such as Google Scholar, ResearchGate, SINTA, DOAJ, and Scopus, with publications ranging from 2020 to 2025. Articles were selected based on criteria such as year of publication, journal index, type of research, and education level. Data analysis was conducted using descriptive qualitative methods. The main findings show that traditional games such as kites, congklak, engklek, gobak sodor, marbles, jump rope, bekel, and damdaman significantly improve students' mathematics learning outcomes in the cognitive, affective, and social domains. These games are able to concretize abstract mathematical concepts, create a fun learning atmosphere, and increase student motivation, active involvement, and social interaction. These findings are expected to contribute to the development of innovative learning methods in elementary schools and encourage the preservation of local culture through traditional games.